Lithium affects the circadian clock in the choroid plexus - A new role for an old mechanism - Liška, Karolína; Dočkal, Tereza; Houdek, Pavel; Sládek, Martin; Lužná, Vendula; Semenovykh, Kateryna; Drapšin, Milica; Sumová, Alena (Biomedicine & pharmacotherapy, 2023)
Lithium is an effective mood stabilizer, but the mechanism of its therapeutic action is not well understood. We investigated the effect of lithium on the circadian clock located in the ventricle barrier complex containing the choroid plexus (CP), a part of the glymphatic system that influences gross brain function via the production of cerebrospinal fluid. The mPer2Luc mice were injected with lithium chloride (LiCl) or vehicle, and their effects on the clock gene Nr1d1 in CP were detected by RT qPCR. CP organotypic explants were prepared to monitor bioluminescence rhythms in real time and examine the responses of the CP clock to LiCl and inhibitors of glycogen synthase kinase-3 (CHIR-99021) and protein kinase C (chelerythrine). LiCl affected Nr1d1 expression levels in CP in vivo and dose-dependently delayed the phase and prolonged the period of the CP clock in vitro. LiCl and CHIR-99021 had different effects on 1] CP clock parameters (amplitude, period, phase), 2] dexamethasone-induced phase shifts of the CP clock, and 3] dynamics of PER2 degradation and de novo accumulation. LiCl-induced phase delays were significantly reduced by chelerythrine, suggesting the involvement of PKC activity. The effects on the CP clock may be involved in the therapeutic effects of lithium and hypothetically improve brain function in psychiatric patients by aligning the function of the CP clock-related glymphatic system with the sleep-wake cycle. Importantly, our data argue for personalized timing of lithium treatment in BD patients.
Keywords: Lithium; Choroid plexus; MPer2Luc mice; Choroid Plexus; Period Circadian Proteins; lithium; myši; Circadian Clocks; cirkadiánní proteiny Period; zvířata; Circadian clock; Animals; Mice; Lithium chloride; plexus chorioideus; cirkadiánní hodiny; Bipolar disorder; GSK3; Circadian Rhythm; cirkadiánní rytmus